2020
DOI: 10.1016/j.heliyon.2020.e05568
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection heat transfer in corrugated annuli with H2O-Al2O3 nanofluid

Abstract: The present work includes a numerical study of natural convection heat transfer in symmetrical and unsymmetrical corrugated annuli filled with H 2 O-Al 2 O 3 nanofluid. In this study, higher and lower temperatures were kept constant at inner and outer cylinders of the annulus; respectively. Eight mathematical models with an aspect ratio of 1.5 were developed to find the best model giving the highest heat transfer rates. The stream-vorticity formulation in curvilinear coordinates was used to solve the governing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…The thermo-physical properties of the nano-fluid are given as shown in Table 1 [ 38 ]. Also, for the nanofluid properties are estimated as follows in Table 2 [ 16 ].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermo-physical properties of the nano-fluid are given as shown in Table 1 [ 38 ]. Also, for the nanofluid properties are estimated as follows in Table 2 [ 16 ].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Also, for the nanofluid properties are estimated as follows in Table 2 [ 16 ].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma et al [17] developed an eco-friendly cutting fluid to promote cleaner and more efficient MQL machining and found that the thermal conductivity and viscosity increased with the mass fraction of nanoparticles. Alumina nanofluid was evaluated as a thermo-fluid with different volume fractions to observe the heat transfer enhancement under several conditions [18][19][20]. In the study of the influence of MQL with Al 2 O 3 nanoparticles on the milling processes of AISID3 steel, it was found that surface roughness decreased by approximately 0.5 mm and improved by nearly 25% [21].…”
Section: Introductionmentioning
confidence: 99%
“…The An Efficient Numerical Simulation of 2D Natural Convection Israa ALESBE et al http://wjst.wu.ac.th effect of the inner square cylinders' positions, sides-ratios, and sizes on radiative and convective heat transfers was discovered to be important. In corrugated annuli filled with nanofluid, a numerical natural convection heat transfer was investigated by Aljabair et al [19]. Eight mathematical models with an aspect ratio of 1.5 were used to find the best model with the highest heat transfer rates.…”
Section: Introductionmentioning
confidence: 99%